Bicuspid Aortic Valve Registry of the Italian Society of Echocardiography and Cardiovascular Imaging (REgistro della valvola aortica bicuspide della società italiana di ECocardiografia e CArdiovascular imaging): Rationale and Study Design - Citro, Rodolfo (J Cardiovasc Echogr, 2018)
BACKGROUND: Bicuspid aortic valve (BAV) is the most common congenital heart disease, affecting 0.5%–2% of the general population. It is associated not only with notable valvular risk (aortic stenosis and/or regurgitation, endocarditis) but also with aortopathy with a wide spectrum of unpredictable clinical presentations, including aneurysmal dilation of the aortic root and/or ascending thoracic aorta, isthmic coarctation, aortic dissection, or wall rupture. METHODS: The REgistro della Valvola Aortica Bicuspide della Società Italiana di ECocardiografia e CArdiovascular Imaging is a retrospective (from January 1, 2010)/prospective, multicenter, observational registry, expected to enroll 3000 patients with definitive diagnosis of BAV made by transthoracic and/or transesophageal echocardiography, computed tomography, cardiovascular magnetic resonance, or at surgery. Inclusion criteria were definitive diagnosis of BAV. Patients will be enrolled regardless of the presence and severity of aortic valve dysfunction or aortic vessel disease and the coexistence of other congenital cardiovascular malformations. Exclusion criteria were uncertain BAV diagnosis, impossibility of obtaining informed consent, inability to carry out the follow-up. Anamnestic, demographic, clinical, and instrumental data collected both at first evaluation and during follow-up will be integrated into dedicated software. The aim is to derive a data set of unselected BAV patients with the main purpose of assessing the current clinical presentation, management, and outcomes of BAV. CONCLUSIONS: A multicenter registry covering a large population of BAV patients could have a profound impact on the understanding of the natural history of this disease and could influence its management.